Rocker-Bogie Suspension System for Planetary Exploration: Modeling - S., Udhayamathi; M., Parthiban; P., Anbarasi M (Journal of Soft Computing Paradigm, 2025)
The Rocker-Bogie Mechanism is chosen for its better stability, efficiency, and adaptability across various challenging terrains. This mechanism helps the rover maintain stability on uneven surfaces through a simple passive suspension linkage system. Navigation is enhanced by using depth cameras with Visual Simultaneous Localization and Mapping (VSLAM) aid. The flexible rocker arms help the rover adapt to various types of rough terrain. The rocker-bogie mechanism is relied upon and employed by leading space research organizations worldwide due to its robustness and adaptability, where the probability of failure in challenging terrains is very low. The rover system presented in this paper was originally designed and developed by a student team. In this study, we review and document the design architecture, control strategy, and performance outcomes of that rover prototype.
Keywords: Rocker-Bogie Mechanism; Uneven Terrain; Space Exploration; Disaster Rescue.